Become a Successful Agricultural Entrepreneur Through the Support Programs for Youth in Indonesia - Siti Nurlaela; Salsadila Panicara; Dicky Mustofa; Hanum Sasilia (Akademi Komunitas Perkebunan Yogyakarta, 2026)
Farmer regeneration is a strategic response to the agrarian crisis in Indonesia, where youth participation in agriculture remains limited. To address this challenge, the Ministry of Agriculture introduced the Young Agricultural Entrepreneurial Development Program (PWMP), which provides capital assistance to young farmers. Despite its potential, the program’s sustainability has been questioned, requiring empirical evaluation. This study employed a quantitative approach to analyze business characteristics, challenges, turnover, networking practices, and sustainability prospects of PWMP beneficiaries. Data were collected through questionnaires distributed to 100 participants, with 73 valid responses obtained between November and December 2024 across several provinces. Findings show that most PWMP-supported enterprises are on-farm businesses (53%), with an average duration of 3.7 years, and are concentrated in Central Java. Major constraints include high dropout rates due to alternative employment choices (48%), low turnover with 44% reporting earnings below IDR 2,000,000, and limited collaboration, as 57% lack business partners. Nevertheless, 52% of enterprises demonstrate potential for sustainability. The study concludes that PWMP has engaged youth in agricultural entrepreneurship but faces structural and managerial challenges. Strengthening the program through mentorship by successful agricultural entrepreneurs is recommended to enhance knowledge transfer, resilience, and long-term viability of youth-led agribusinesses.